The structure and magnetic properties of magnetron sputtered Ni-Mn-Sn ferromagnetic shape memory thin films with different growth conditions. - Liu, Peng. (2011)
In the present study, structural and magnetic properties of Ni-Mn-Sn ferromagnetic shape memory alloy thin film, grown on Si (100) and MgO (100) substrates at different deposition temperatures, argon pressures, powers, and target-substrate distances by magnetron sputtering have been systematically investigated. The crystallization and structural features were studied by atomic force microscopy, scanning electron microscopy and X-ray diffraction. The structural field induced transition from martensite to austenite was observed by the physical properties measurement system. The investigations show the films exhibit ferromagnetic behavior at temperatures below Curie temperature (TC). Thermomagnetization curves and XRD results reveal the influences of the deposition temperature on the thin film structures.